A novel missense mutation in the NADPH binding domain of CYBB abolishes the NADPH oxidase activity in a male patient with increased susceptibility to infections. (November 2016) - Khan, Taj Ali; Kalsoom, Kalsoom; Iqbal, Asif; Asif, Huma; Rahman, Hazir; Farooq, Syed Omar; Naveed, Hassan; Nasir, Umar; Amin, Muhammad Usman; Hussain, Mubashir; Tipu, Hamid Nawaz; Florea, Andrei
Abstract: Chronic granulomatous disease (CGD) is a primary immunodeficiency caused by mutations in the five structural genes (CYBB, CYBA, NCF1, NCF2, and NCF4) that typically results in a decrease in function or inability to generate a respiratory burst, leading to defective killing of pathogens, including fungi and intracellular bacteria. Mutations in CYBB, encoding the gp91phox (also known as NOX2) result in X-linked CGD account for approximately 65% of CGD cases. Here, we aimed the characterization of a novel missense mutation c.1226C > A/p.A409E in the CYBB gene in a patient with X-linked CGD. Relevant clinical data of a male patient whose family was positive for XCGD was reviewed. Oxidative burst and NADPH protein expression was evaluated by flow cytometry, while Genetic analysis was performed by Sanger sequencing. Monocyte-derived macrophages (MDMs) were evaluated for their capacity for phagocytosis and growth suppression of the intracellular Mycobacterium tuberculosis ( M. tuberculosis ). We thus report the absence of an oxidative burst in the phagocytes of the patient. Flow cytometry evaluation revealed a normal expression of NADPH oxidase components in neutrophils and genetic analysis proved the existence of a novel missense c.1226C > A mutation in the CYBB gene resulting in p.A409E. Further, we have showed that the patient's MDMs were unhindered in their ability to take up mycobacteria normally. Instead, the MDMs failed to control the intracellular proliferation of M. tuberculosis, a phenotype that improved in the presence of recombinant human interferon-gamma (rhIFN-γ). This work expands the genetic spectrum of X-linked CGD and demonstrates improvement in macrophage function in X91 + CGD patient by rhIFN-γ.